Pengaruh Digital Marketing dan Promosi terhadap Keputusan Pembelian Geprek Bakar Tuku Sambal di Jambi - Muryati Muryati; Sri Rosmawati; Wahya Iffa Lubis (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Geprek Bakar Tuku Sambal is one of the culinary delights in the city of Jambi, which sells a food menu that is in great demand by the people in the city of Jambi. This research aims to determine the partial and simultaneous effect of Digital Marketing and Promotion variables on purchasing decisions of Geprek Bakar Tuku Sambal, besides it is also to find out the most dominant variable in making purchasing decisions for Geprek Bakar Tuku Sambal. This research is comparative causal research with a quantitative approach. The variables in this study are Digital Marketing, Promotion, and Purchasing Decisions. The population of this research is regular customers of Geprek Bakar Tuku Sambal, with 69 respondents. The results of the study indicate that the partial influence of Digital Marketing and Promotion of each variable has a positive and significant effect on the decision, while simultaneously all variables X1 and X2 have a positive and significant effect on the buying decision of Geprek Bakar Tuku Sambal. The results of the analysis show that the value Adjusted R Square of 0.719 means that the variable Digital Marketing and Promotion 71.9% influences the purchasing decision of Geprek Bakar Tuku Sambal by 28.1% is influenced by other variables that were not examined in this study.